2017
DOI: 10.1515/geo-2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

“Urban geosites” as an alternative geotourism destination - evidence from Belgrade

Abstract: Abstract:The research aimed at testing the combination of GAM/M-GAM models (Geosite Assessment Model/Modified Geosite Assessment Model) on selected geoheritage sites (geosites) of great scientific significance and geotourism potential. Testing was done on eight sites in the City of Belgrade (Serbian capital), an area which has significant potential for geotourism development in typical urban conditions. For this purpose, an assessment scale was used to highlight differences and similarities between main and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 18 publications
(22 reference statements)
0
22
0
Order By: Relevance
“…It is highly appreciated with the name of "smokeless industry" and prioritized as a crucial economic driving force [2]; and it is also called the "green economy" [6]. Everett and Aitchison [7] and Demirović et al [8] found a strong relationship between tourism and the local life, culture and heritage, while Petrović et al [9] discovered that tourism is closely related to natural attractions. As a consequence, tourism can improve the national identity [6] and bring huge benefits to society [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is highly appreciated with the name of "smokeless industry" and prioritized as a crucial economic driving force [2]; and it is also called the "green economy" [6]. Everett and Aitchison [7] and Demirović et al [8] found a strong relationship between tourism and the local life, culture and heritage, while Petrović et al [9] discovered that tourism is closely related to natural attractions. As a consequence, tourism can improve the national identity [6] and bring huge benefits to society [10].…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable tourism can enhance the identity of the entire country, because it is strongly related to ways of local production, locals' life, cultural celebration, heritage [14][15][16], and natural attractions [17] in rural or (peri-)urban settings. Moreover, this type of tourism is an alternative of great interest for different segments of tourists whose preferences include the sustainability of tourist spaces when planning their trips.…”
Section: Introductionmentioning
confidence: 99%
“…Problems are related to the traditional method of exposition (samples and description). Taking inspiration from previous experiences, to which others have been added over time as highlighted in the references list [29][30][31][32][33][34] some already tested items were proposed in the exhibition. One of the most successful approaches is to highlight and illustrate some of the stones used for historical buildings [35,36].…”
Section: Methodsmentioning
confidence: 99%